Practising Inquiry-Based Instruction (IBI) in Tanzanian Early Years Education: An Assessment of Teachers’ Views and Curriculum Contexts - Mwakyusa Kejo, Subilaga; Manyonyi Machumu, Maregesi; Kinyota, Mjege (Papers in Education and Development, 2024)
This study explored teachers’ conceptions and practices of practising inquiry-based instruction (IBI) in early years education and how the curriculum supports IBI integration. Employing a qualitative approach, this study generated data from 37 purposively selected early years teachers from ten schools in Dar es Salaam using interviews and document analysis. It was found that teachers have a narrow conception of IBI. Moreover, teachers rarely integrate IBI in their classrooms due to large classes, unsupportive curriculum contexts, and limited understanding of IBI. Furthermore, the findings revealed that though the curricula objectives and content permit integration of IBI, overemphasis on academic skills such as literacy and numeracy skills limits the integration of IBI. Keywords: early years, inquiry-based learning, in-service teachers, Tanzania